Small intestinal bacterial overgrowth among patients with celiac disease unresponsive to a gluten free diet - A. Safi, Mohammad-Ayman; Jiman-Fatani, Asif A.; Saadah, Omar I. (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Little is known about the relationship between small intestinal bacterial overgrowth (SIBO) and celiac disease (CeD) in patients who are unresponsive to a gluten-free diet (GFD). This study aimed to determine the SIBO prevalence in patients with CeD who are unresponsive to a GFD.Materials and Methods: We conducted a case-control study from July 2012 to September 2014. We included 32 patients with CeD who were unresponsive to a GFD and 52 healthy age- and sex-matched controls. Demographic, clinical, and laboratory data were obtained from patients’ medical records. Antitissue transglutaminase antibody determined by enzyme-linked immunosorbent assay was recorded, and lactulose hydrogen breath test (LHBT) was used to detect SIBO in all participants. Microbiological analysis, including jejunal aspirates obtained using upper endoscopy, was performed for only 20 patients with CeD. Results: A total of 10 (31%) of 32 patients with CeD and 4 (7.7%) of 52 controls tested positive for LHBT, with a statistically significant difference (p=0.007). Of 20 cultures, 3 (15%) were positive with no statistically significant correlation between the cultures and LHBT (p=0.05). In a subgroup analysis of children who were 18 years old or younger, 7/24 (29.2%) patients with CeD had a positive LHBT compared with 3/32 (9.4%) controls, but this difference was not statistically significant (p=0.08).Conclusion: The prevalence of SIBO was 31% in unresponsive patients with CeD according to LHBT and 15% in the quantitative culture of the jejunal aspirate, which is comparable with the published Western literature